Improving outcomes for type 2 diabetes mellitus patients in Selangor: a study on health literacy intervention and its effectiveness - Mahmud, Aidalina; Ismail, Suriani; Shariff Ghazali, Sazlina; Wan Hamdzan, Wan Farzana Fasya (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2024)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a metabolic disorder that can be controlled by self-care which includes medication adherence and dietary adjustments. However, health literacy can impede successful self-care, leading to suboptimal blood sugar management and a diminished quality of life. This research aimed to evaluate the impact of a health literacy intervention on enhancing glycaemic control, health literacy, and the quality of life related to diabetes in T2DM patients residing in a rural Malaysian region. Materials and methods: A two-armed, single-blinded randomized controlled trial was conducted among 250 diabetic patients on medication, aged 18 years and more who were enrolled from a health clinic in Selangor. The intervention group received a health literacy module, a healthy-plate guide, and a flip chart for self-management. The control group received standard diabetic education. Primary outcomes assessed glycaemic control (HbA1c levels), health literacy (HLS-EU-Q47 tool), and diabetes-related quality of life (DQoL-M) at baseline and three months post-intervention. The study is registered in the Australian New Zealand Clinical Trials Registry (ACTRN12619001725156). Results: The result showed a statistically significant improvement in Glycaemic Control in the intervention group (F=4.003, p=0.046), but not in the control group. Health Literacy and the satisfaction domain of Diabetes Quality of Life scores were higher in the intervention compared to the control group, however, the differences between the groups were not statistically significant. Conclusion: The intervention in this study improved glycaemic control of diabetic patients. Nonetheless, there is a need for personalized diabetes care, ongoing support, and further research to enhance outcomes.